Adaptation of the Romanomermis culicivorax CCA-Adding Enzyme to Miniaturized Armless tRNA Substrates - Hennig, Oliver (Int J Mol Sci, 2020)
The mitochondrial genome of the nematode Romanomermis culicivorax encodes for miniaturized hairpin-like tRNA molecules that lack D- as well as T-arms, strongly deviating from the consensus cloverleaf. The single tRNA nucleotidyltransferase of this organism is fully active on armless tRNAs, while the human counterpart is not able to add a complete CCA-end. Transplanting single regions of the Romanomermis enzyme into the human counterpart, we identified a beta-turn element of the catalytic core that—when inserted into the human enzyme—confers full CCA-adding activity on armless tRNAs. This region, originally identified to position the 3′-end of the tRNA primer in the catalytic core, dramatically increases the enzyme’s substrate affinity. While conventional tRNA substrates bind to the enzyme by interactions with the T-arm, this is not possible in the case of armless tRNAs, and the strong contribution of the beta-turn compensates for an otherwise too weak interaction required for the addition of a complete CCA-terminus. This compensation demonstrates the remarkable evolutionary plasticity of the catalytic core elements of this enzyme to adapt to unconventional tRNA substrates.